Implementation of the Principle of Res Judicata Pro Varitate Habetur in the Constitutional Court Decision Number 90/PUU-XXI/2023 - Riyah, Barokatun Nuris Syah (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
The principle of res judicata pro varitate habitur is a principle that explains that the judge's decision must be considered correct before there is a higher judge's decision to annul it. However, this principle is difficult to apply to the Constitutional Court's ruling, whose decision is considered final and binding, without a mechanism for correction. This condition raises concerns, particularly in the Constitutional Court's decision, which is regarded as flawed; therefore, this study is essential for formulating the limits of applying this principle in Constitutional Court Decision No. 90/PUU-XXI/2023. This research employs a normative legal approach, incorporating legislative, conceptual, and case studies. Research data was obtained from literature studies in the form of laws, rulings, books, research, and journal articles. The collected data is analyzed deductively. The results of the study explain that the principle of Res judicata pro varitate habitur cannot be applied if it is proven that there is an excess of authority between state institutions in Indonesia. The Constitutional Court's decision Number 90/PUU-XXI/2023 regarding the age limit for presidential and vice presidential candidates is considered problematic because it is formally considered flawed, one of its judges is proven to have violated the code of ethics, and is substantially considered to exceed the authority of the Constitutional Court as a negative legislator by creating a new norm that should be the realm of open legal policy House of Representatives. Because the reconstruction of legislation in Indonesia is necessary to regulate in a clear and measurable way extraordinary conditions that allow exceptions to the principle of Res judicata in the decisions of the Constitutional Court in order to maintain a balance between legal certainty.